Relationship Between Acylcarnitine and the Risk of Retinopathy in Type 2 Diabetes Mellitus - Wang, Wan-Ying; Liu, Xu; Gao, Xiao-Qian; Li, Xin; Fang, Zhong-Ze (Frontiers in Endocrinology, 2022)
Objective: Diabetic retinopathy is a common complication of diabetes mellitus. Due to the limited effectiveness of current prevention and treatment methods, new biomarkers are urgently needed for the prevention and diagnosis of DR. This study aimed to explore the relationships between plasma acylcarnitine with DR in type 2 diabetes (T2D). Methods: From May 2015 to August 2016, data of 1032 T2D patients were extracted from tertiary hospitals. Potential non-linear associations were tested by binary logistic regression models, and ORs and 95% CIs of the research variables were obtained. Correlation heat map was used to analyze the correlation between variables. The change of predictive ability was judged by the area under the receiver operating characteristic curve. Results: Of the 1032 patients with T2D, 162 suffered from DR. After adjusting for several confounding variables, C2 (OR:0.55, 95%CI:0.39-0.76), C14DC (OR:0.64, 95%CI:0.49-0.84), C16 (OR:0.64, 95%CI:0.49-0.84), C18:1OH (OR:0.51, 95%CI:0.36-0.71) and C18:1 (OR:0.60, 95%CI:0.44-0.83) were negatively correlated with DR. The area under the curve increased from 0.794 (95% CI 0.745 to 0.842) to 0.840 (95% CI 0.797 to 0.833) when C2, C14DC, C18:1OH and C18:1 added to the traditional risk factor model. Conclusion: There was a negative correlation between C2, C14DC, C16, C18:1OH, and C18:1 and the risk of retinopathy in patients with T2D. C2, C14DC, C18:1OH, and C18:1 may be new predictors and diagnostic markers of DR.